Role of microRNA in metabolic shift during heart failure - Pinti, Mark V. (Am J Physiol Heart Circ Physiol, 2017)
Heart failure (HF) is an end point resulting from a number of disease states. The prognosis for HF patients is poor with survival rates precipitously low. Energy metabolism is centrally linked to the development of HF, and it involves the proteomic remodeling of numerous pathways, many of which are targeted to the mitochondrion. microRNAs (miRNA) are noncoding RNAs that influence posttranscriptional gene regulation. miRNA have garnered considerable attention for their ability to orchestrate changes to the transcriptome, and ultimately the proteome, during HF. Recently, interest in the role played by miRNA in the regulation of energy metabolism at the mitochondrion has emerged. Cardiac proteome remodeling during HF includes axes impacting hypertrophy, oxidative stress, calcium homeostasis, and metabolic fuel transition. Although it is established that the pathological environment of hypoxia and hemodynamic stress significantly contribute to the HF phenotype, it remains unclear as to the mechanistic underpinnings driving proteome remodeling. The aim of this review is to present evidence highlighting the role played by miRNA in these processes as a means for linking pathological stimuli with proteomic alteration. The differential expression of proteins of substrate transport, glycolysis, β-oxidation, ketone metabolism, the citric acid cycle (CAC), and the electron transport chain (ETC) are paralleled by the differential expression of miRNA species that modulate these processes. Identification of miRNAs that translocate to cardiomyocyte mitochondria (miR-181c, miR-378) influencing the expression of the mitochondrial genome-encoded transcripts as well as suggested import modulators are discussed. Current insights, applications, and challenges of miRNA-based therapeutics are also described.